Energy Conversion and Dissipation at Dipolarization Fronts: A Statistical Overview. Issue 22 (25th November 2019) - Zhong, Z. H.; Deng, X. H.; Zhou, M.; Ma, W. Q.; Tang, R. X.; Khotyaintsev, Y. V.; Giles, B. L.; Russell, C. T.; Burch, J. L.
Abstract: Dipolarization fronts (DFs) are important for energy conversion, particle acceleration, and flux transport in the magnetotail. The partition of energy conversion between ions and electrons and the energy dissipation at DFs are not well understood. In this paper, we present a statistical study of energy conversion and dissipation of 122 DFs observed by Magnetospheric Multiscale mission in the magnetotail. Statistically, electromagnetic energy transfers to plasma at DF. The released energy is mainly transferred to ions rather than electrons. On average, ions gain energy across the whole DF, while electrons gain energy at the leading part but lose energy at the trailing part of DFs. Joule dissipation J · (E+ve × B) can be either positive or negative at DFs, and its average value is very small. The kinetic energy dissipation parameter Pi − D does not exhibit clear signatures at the DFs; hence, it is not suitable for quantifying the energy dissipation at DF. Key Points: Statistical study of the energy conversion and dissipation at DFs observed by MMS Electromagnetic energy released at DF mainly goes to heat and accelerate ions Average Joule dissipation across DF is very small, and the parameter Pi − D is not suitable for quantifying the energy dissipation at DF